The Effect of Using Ice Breaking on Learning Motivation of Elementary School Students in Learning Science - Riska Putri Taupik (Universitas Tidar, 2023)
This research was conducted due to the low learning motivation of elementary school students in participating in class learning, especially in science learning. One of the causes of low learning motivation is the lack of interesting innovations in learning, so that students tend to get bored and bored in learning. This low motivation results in low scientific literacy abilities of students. This study aims to determine the effect of using ice breaking on students' learning motivation and scientific literacy abilities. This research was conducted in an elementary school in a district in West Sumatra. This type of research is quantitative in the form of a quasi-experimental design. The data analysis used quantitative analysis using the Paired Sample T-Test. Based on the pretest results, the average motivation score of the experimental class that applied Ice Breaking was 49.842 and the post-test motivation score of the experimental class was 82.631. Based on the results of hypothesis testing conducted with the Paired Sample T-Test, tcount = 3.8421 and ttable 2.028 with a significant level of 5%. Thus t'count = 3.8421 > ttable = 2.028, it can be concluded that there is an effect of using Ice Breaking on Learning Motivation of Elementary School Students in Learning Science.